Clinical Utility of Targeted Next-Generation Sequencing in the Evaluation of Low-Grade Lymphoproliferative Disorders. Issue 3 (13th March 2021) - Jajosky, Audrey N; Havens, Nathaniel P; Sadri, Navid; Oduro, Kwadwo A; Moore, Erika M; Beck, Rose C; Meyerson, Howard J
Abstract: Objectives: We investigated the usefulness of a custom-designed 31-gene next-generation sequencing (NGS) panel implemented on a routine basis for the evaluation of low-grade lymphoproliferative disorders (LPDs). Methods: In total, 147 blood, bone marrow, and tissue specimens were sequenced, including 81% B-cell, 15% T-cell, and 3% natural killer (NK)–cell neoplasms. Results: Of the cases, 92 (63%) of 147 displayed at least one pathogenic variant while 41 (28%) of 147 had two or more. Low mutation rates were noted in monoclonal B-cell lymphocytoses and samples with small T- and NK-cell clones of uncertain significance. Pathogenic molecular variants were described in specific disorders and classified according to their diagnostic, prognostic, and potential therapeutic value. Diagnostically, in addition to confirming the diagnosis of 15 of 15 lymphoplasmacytic lymphomas, 10 of 12 T large granular lymphocytic leukemias, and 2 of 2 hairy cell leukemias (HCLs), the panel helped resolve the diagnosis of 10 (62.5%) of 16 challenging cases lacking a specified diagnosis based on standard morphology, phenotype, and genetic analysis. Conclusions: Overall, implementation of this targeted lymphoid NGS panel as part of regular hematopathology practice was found to be a beneficial adjunct in the evaluation of low-grade LPDs.